Relationship Between Vertebral Fractures, Bone Mineral Density, and Osteometabolic Profile in HIV and Hepatitis B and C-Infected Patients Treated With ART - Dalla Grana, Elisa; Rigo, Fabio; Lanzafame, Massimiliano; Lattuada, Emanuela; Suardi, Silvia; Mottes, Monica; Valenti, Maria Teresa; Dalle Carbonare, Luca (Frontiers in Endocrinology, 2019)
Objective: Aim of our study was to evaluate the alterations of bone metabolism and the prevalence of fractures in the population with HIV and hepatitis B and C seropositivity in treatment with antiretroviral drugs. Design: we performed radiographs of the dorso-lumbar spine to detect vertebral deformities Methods: We selected 82 patients with diagnosis of HIV, HBV, HCV infection. In all these patients biochemical examinations of phospho-calcium metabolism and in 71 of them densitometric data evaluation were also performed. We also evaluated radiographs of the dorso-lumbar spine, to analyze the presence of any vertebral deformity and to define its severity. Results: The prevalence of hypovitaminosis D in the population was 53%, while the prevalence of osteoporosis and osteopenia was 14% and 48%, respectively. The T-score threshold at the lumbar spine to detect patients at a higher risk for fractures was -1.7 SD. The viral load and the CD4+ cell count were directly and inversely correlated respectively with the number and severity of fractures. Antiretroviral therapy regimen containing TDF and PI was a significant determinant of the presence of vertebral deformities. The use of bone-affecting drugs was associated with lower levels of vitamin D and higher bone turnover levels compared to other drugs. Conclusions: HIV patients suffer from bone fragility, particularly at the spine, independently by bone density level. In this population, the T-score threshold for the risk of fracture is higher than in the general population. This value could be used as a cut-off, below which the execution of a radiography of the dorso-lumbar spine is indicated to evaluate the presence of vertebral fractures.